Styrofoam Biodegradation By Soil Bacteria Isolated From Landfill Site In Hospital: Literature Review - Putra, Heri Shatriadi Candra; Rashid, Norhashima Abd; Said, Faridah Mohd (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Introduction: Styrofoam is commonly used in food and beverage packaging. Styrofoam or polystyrene is made from styrene and benzene. The migration of benzene from packaging materials into foods can cause various diseases. One effort to reduce styrofoam waste is possible by searching for bacteria that can degrade styrofoam naturally. Potential source of place where the bacteria will be discovered is the landfill site in hospital. Material and Methods: This research applied exploratory methods through descriptive qualitative analysis. The stages of the study consisted of biodegradation testing using the Winogradsky method, calculation of the percentage of dry weight loss of Styrofoam, physical analysis using Scanning Electron Microscope (SEM), and analysis of changes in functional groups using FTIR. This study discovered 4 species of polystyrene degrading bacteria, namely Pseudomonas aeruginosa, Bacillus amyloliquefaciens, Bacillus cereus and Bacillus firmus. Results: The percentage of dry weight reduction of polystyrene was shown in the eighth week which reached 18.23% and physical analysis by Scanning Electron Microscope (SEM) indicated that the process of degradation by soil bacteria resulted in formation of pores on the surface of styrofoam. Conclusion: Functional group analysis produced a simpler functional groups after the degradation as marked by the appearance of C-O functional groups at wavenumber of 1,030.02 cm-1. The use of these polystyrene degrading bacteria from Sarimukti landfill can be recommended as an environmentally friendly method for reducing styrofoam waste.